The Effect of Honey on The Level of Dysmenorrhea Pain in Nursing Students of Muhammadiyah University Tasikmalaya - Herdiani, Ida; Restiana, Nia; Ariyani, Hana; Febriyani, Ria (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Dysmenorrhea is the most common gynecological disorder among women of all ages and races. Dysmenorrhea is defined as pain during menstruation that is accompanied by cramping and centered in the lower abdomen. Dysmenorrhea can cause a number of problems, including activity limitation, decreased academic performance, and difficulty sleeping so that it can interfere with life activities.   Currently, there is a need for the use of herbs and alternative medicine to overcome dysmenorrhea, one of which is using honey which can reduce menstrual pain. The purpose of this study was to determine the effect of honey on the level of dysmenorrhea pain in nursing students at Muhammadiyah Tasikmalaya University. This research method uses Quasi Exsperimen research method with Pre-Experimental design with one group pre-test and post-test design approach. This research was conducted at the University of Muhammadiyah Tasikmalaya.  Respondents measured pain levels during dysmenorrhea before and after honey administration. The results showed that giving honey had an effect on reducing menstrual pain or dysmenorrhea in nursing students as indicated by a value of P = 0.000.  The conclusion is that there is a change in the intensity of menstrual pain before and after giving honey.  Suggestions are expected that the results of this study can be implemented by further researchers as an alternative to dysmenorrhea pain.